Relationship Between Lipid Profiles and Serum Electrolytes in Cardiac Patients: A Gender Perspective - Muzzamal, Hira; Yonus, Muhammad Awais; Haqqi, Aleena; Saleem, Mahjabeen Saleem (Journal of Basic and Emerging Sciences, 2024)
Cardiovascular diseases (CVD), include ischemic heart disease, peripheral vascular disease and stroke, and are the primary causes of mortality in the majority of high, low, and middle-income countries. Cardiovascular disease incidences are resulted by the hereditary as well as environmental factors. Disparity of the lipid profile and electrolytes imbalance poses serious risk to CVD. The objective of this study was to find the gender base relationship between lipid profile and serum electrolytes in cardiac patients. 45 cardiovascular patients were enrolled in this cross-sectional study. The serum samples were used for the evaluation of lipid profile and serum electrolytes. On the basis of statistical analysis, 66.6% of cardiac patients had dyslipidaemia, while 33.4% showed no such symptoms. Meanwhile 28.8% of cardiac patients had electrolyte imbalance and 71.2% of patients had normal electrolyte values. Statistically significant differences were observed for TC (p = 0.028) and HDL (p = 0.024) with males showing lower levels of TC and HDL as compared to females indicating that gender may influence lipid metabolism and associated cardiovascular risk. The study suggested that dyslipidemia was a chief contributing factor in the etiology of cardiovascular diseases being prominent in males.